HR LINE MANAGER’S REFLECTIONS ON HRM EFFECTIVENESS THROUGH HR ROLES AND ROLE STRESSORS (The South East European Journal of Economics and Business, 2019)
The present study examines the relationship between HR roles and HR role stressors in determining the effectiveness of HRM. A massive primary survey was conducted in which 153 line managers of Malaysia’s manufacturing companies participated, the data were analyzed through structural equation modeling (SEM) using Smart PLS. The significant findings of the study reveals that top management support provided insights to the conditions needed to avoid perception of HR role stressors on line managers. Results also revealed that there is a mediation effect of HR overload by line managers, however, no mediation effect has influenced on HR ambiguity. Top management support has moderated the relationship of HR roles on HR role ambiguity.